Happiness, Economy and Institutions - Bruno S. Frey; Alois Stutzer (Center for Economic Studies and ifo Institute (CESifo), 2000)
A cross-regional econometric analysis suggests that institutional factors in the form of direct democracy (via initiatives and referenda) and of federal structure (local autonomy) systematically and sizeably raise s elf-reported individual well-being. This positive effect can be attributed to political outcomes closer to voters' preferences, as well as to the procedural utility of political participation. Moreover, the results of standard microeconometric well-bein g functions previously published for other countries are generally supported. Unemployment has a strongly depressing effect on happiness. A higher income level raises happiness, however, only to a small extent.
Keywords: 330; Subjective well-being; institutions; direct democracy; unemployment